Usability Evaluation for Mobile Health Application: Systematic Literature Review - Septiani, Winnie; Rahmawati, Novia; Safitri, Dian Mardi; Luis, Martino (SINERGI, 2024)
Health applications have unique characteristics compared to other applications. This application is needed to support the health of users/families with various facilities provided according to their functions and objectives. Usability measurement is carried out to evaluate the successful use of the application using various usability criteria. This study aimed to identify, analyze, and synthesize the usability evaluation of a mobile health application. The review was carried out on 65 selected papers from 799 usability papers from the Web of Science and Scopus in the 2013 to 2023 time period. The Systematic Literature Review approach used is the Preferred Reporting Item for Systematic Reviews and Meta-Analysis (PRISMA). Based on the review results, it was identified that usability measurement on mobile health applications aims to validate system design, compare usability methods, improve application performance, and evaluate usability. Meanwhile, mHealth apps mostly function for treatment and self-care/self-management. Most of the reviewed papers used the general public as respondents. The respondents or participants in these studies are diverse and can be categorized into five groups: patients, healthcare professionals, older adults, experts, and the general public. Most of the research aims to evaluate usability with the most widely used method, the System Usability Scale, which is equipped with other supporting methods.